2012
DOI: 10.1103/physrevlett.109.125502
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Stability Constrains Force and Pair Distributions at Random Close Packing

Abstract: The requirement that packings of hard particles, arguably the simplest structural glass, cannot be compressed by rearranging their network of contacts is shown to yield a new constraint on their microscopic structure. This constraint takes the form a bound between the distribution of contact forces P (f ) and the pair distribution function g(r): if P (f ) ∼ f θ and g(r) ∼ (r − σ0) −γ , where σ0 is the particle diameter, one finds that γ ≥ 1/(2 + θ). This bound plays a role similar to those found in some glassy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
238
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(262 citation statements)
references
References 37 publications
22
238
1
Order By: Relevance
“…It was recently shown that mechanical stability requires the distribution of contact forces in packings of frictionless spheres to vanish at small forces [23], as observed in Ref. [25].…”
Section: Weakest Force In the Volume Cmentioning
confidence: 82%
See 1 more Smart Citation
“…It was recently shown that mechanical stability requires the distribution of contact forces in packings of frictionless spheres to vanish at small forces [23], as observed in Ref. [25].…”
Section: Weakest Force In the Volume Cmentioning
confidence: 82%
“…Finally, in Sec. VIII the marginal stability criterion observed for jammed packing [23,24] is rederived in flows.…”
Section: Introductionmentioning
confidence: 99%
“…For small forces we find, P(F) to rise exponentially, as approximately F 3/2 . Wyart [15], showed that the exponent is determined by the pair distribution function g(r). However, in our small system with a fixed particle configuration, g(r) is undersampled, so the question arises what the exponent is set by here.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, its value does not depend on the preparation protocol of the isostatic state: up to error bars, equal values are found from compression of hard spheres [32], shear-jammed hard disks [35], and decompression of soft spheres [33,36] 1 . The exponent θ e can be shown to control the stability of the solid phase [32,37,38]. Recently replica calculations in infinite dimension on the force distribution [36,39,40] led to the prediction [33]:…”
Section: Introductionmentioning
confidence: 99%